(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Nowadays, a lot of accidents occur at U-turn spreading at different types of roads in Al-Najaf city. Moreover, the most severe congestion also has been seen in these U-turn during peak hours. Therefore, this study has focused on studying the characteristics of these U-turns in terms of flow for different movements for each site. The manufactured vantage point has been made to capture the weaving movement along these sections using video camera. Simulation model called S-Paramics has been used after calibrating it with filed data collected from several U-turn sites. The simulated model has been used to select the best location for the U-turn regarding to the nearest access point. The results show that the distance should be not less than 300m in order to avoid congestion. In addition, new improvements have been suggested to correct violated behaviors of drivers.